Ciclo de crescimento dos botões florais de café (Coffea arabica L) - Frederico, Donato; Maestri, Moacyr (Revista Ceres, 2025)
The growth of flower buds of coffee under field conditions in Viçosa, Minas Gerais (Brazil) was studiedin the year of 1967. Between 74-100 buds were collected weekly for length, dry matter and fresh weight determinations.